Special tax on illegally acquired property - Baturan, Luka O; Milošević, Goran (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
Abstract: The National Assembly of the Republic of Serbia has adopted the Law on Determining the Origin of Property and Special Tax. With the "new" legal solution on determining the origin of property and special tax, Serbia seeks to protect the fiscal and other interests of the state based on the income of natural persons caused by abuse resulting in the possession of property that cannot be justified by legal income. Since the Law on Determining the Origin of Property and Special Tax introduces a new "special tax", it an opportunity to define the basic contours of this tax, and to give guidelines for practical application, as well as for the possible correction of the Law.  Keywords: special tax, illegally acquired property, undeclared income, real property tax, excess profits tax.
Keywords: special tax; illegaly acquired property; undeclared income; real property tax; excess profits tax